Increased vulnerability of older adults to DM and its CVD complications: proposal for assessment, management and monitoring by diagnostic methods - Nwose, Ezekiel Uba; Bwititi, Phillip Taderera; Richards, Ross Stuart (International Journal of Research in Medical Sciences, 2017)
The national institute of health on aging has made research funding calls for basic, clinical and epidemiological studies into the increased vulnerability of older adults to diabetes mellitus and its cardiovascular complications. One of the indicated outcomes is the impact of age on diagnosis and management of the disease co-morbidity, including elucidation of the role of aging mechanisms that underlie the increased vulnerability of older adults. A cursory review of literature reveals that although there is information about aging and oxidative stress, little has been validated for adoption in the context of pathology-based evidence. Therefore, the objective of this hypothesis paper is to revisit the topic of ‘biochemical basis of metabolism’ in aging and diseases. The concepts of ‘aging-induced oxidative stress’ and ‘antioxidant-vitamins’ basis of diabetes progression’ are briefly linked to propose that increase in oxidative damage is a potential additive outcome underlying increased vulnerability of older adults to diabetes mellitus and its cardiovascular complications. Further, the prospect of oxidative damage indices is re-presented as a hypothesis for validation to provide pathology evidence-based guidance to seek appropriate clinical laboratory criteria. The validation process would delineate reference values in vulnerable older adults relative to young and middle aged groups with a view to enable assessment, management and monitoring by diagnostic methods.